The jurisprudence of reality and its impact in guiding the problem of hadith rulings. Sighting the crescent of Ramadan with modern astronomical devices - an example - Asma' Shafiq Shaeban,; Iman M. Farhan, (Islamic Sciences Journal, 2024)
ABSTRACT The term jurisprudence of reality is one of the common and widespread terms in the contemporary arena. The nation’s scholars have stressed the importance of jurisprudence of reality in understanding the text and reaching the intent of the lawgiver, as Islamic law took into account the conditions and facts that prevailed in many rulings, and that jurisprudence of reality is of great importance to those concerned with understanding The Sharia text, because it represents one of the ways to reach the intention of Allah Almighty in revealing the rulings after understanding the text, especially in understanding the problem of the hadiths about the rulings, since the Sharia texts came to address the people and organize their conditions and dealings, so it is unfair for the rulings to be revealed without taking into account the nature of their lives, their customs, and their differences, and for this reason The jurisprudence of reality had an important place among the nation’s mujtahids and scholars. In this research, I presented an applied model of the impact of the jurisprudence of reality in guiding the problem of hadith rulings, and the ruling on proving the sighting of the Ramadan crescent with modern astronomical devices.